Schopenhauer on Death and Suicide - Papadaki (Λίνα Παπαδάκη), Lina (Bioethica, 2020)
Schopenhauer is portrayed as the philosopher of pessimism, and for good reason. For him, life is suffering where ‘ultimately death must triumph’ (The World as Will and Representation vol. I, 311). However, his pessimism fades away when he contemplates death. He argues enthusiastically that, far from being an evil, death is in fact a friend we should welcome. Moreover, he believes it is possible for human beings to use their knowledge to fight the fear of death. Interestingly, however, at the point where the reader expects a philosophical defense of suicide, Schopenhauer vehemently argues against it. Suicide to avoid pain and suffering, according to him, is a mistake, a futile, foolish and egoistic act. Not only does suicide not offer a genuine solution to suffering, but also it hinders true salvation, the denial of the will. In this paper, I argue that Schopenhauer’s condemnation of suicide is in fact at odds with his views on death and can weaken his argumentation about why we must not fear death. It is my belief that Schopenhauer’s views on suicide stem - quite ironically - from his being, at times, overly optimistic about the possibility of genuine salvation. When it comes to freeing ourselves from the will, however, we are better off pessimists. This, I explain, will allow us to at least keep our optimism regarding death and find solace in the knowledge that - be it by old age, illness, accident, suicide or any other cause - death is not to be feared.